Investors’ Responses on SOE’s Liquidity Risk Disclosures: Case of Indonesia - Ira Geraldina; Hilda Rossieta; Ratna Wardhani (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study aims to examine the value relevance of liquidity risk disclosure of Indonesia listed state owned enterprises after Indonesia Statement of Financial Accounting Standard, Disclosure of Financial Instruments (Revised in 2010 and 2014). This study uses 20 Indonesia listed state owned enterprises during period of 2012-2017 or 115 firm years as final samples. Using panel data analysis, this study shows that liquidity risk disclosure is relevant information for investors in Indonesia stock exchange. Investors response differently on liquidity risk disclosure before and after the announcement windows period of financial reports. The main contribution of this is examining the value relevance of liquidity risk disclosure of Indonesia listed state owned enterprises.